Communication for Industrial Heritage Preservation in Anshan City, China - Zhuoran, Wang; Yossakrai, Asst.Prof.Dr.Kanokrat; Patananukit, Dr. Nutcha (Journal of Dhamma for Life, 2023)
This research aimed to investigate the communication strategies and processes employed to promote industrial heritage in Anshan city, China, using a qualitative research approach. The study involved key interviews with six groups: local wisdom people in industrial heritage, academic experts, government officials, artists recognized in the field, government communication officials, and tourists. The research revealed two main findings: Communication Situation of Industrial Heritage in Anshan City: The study, drawing on collective memory and Adorno’s theories, found a certain level of public memory and recognition of industrial heritage in Anshan. However, a need to enhance public awareness and appreciation was identified. Challenges in communication were noted, particularly among younger generations who showed less interest and awareness. The study suggests strengthening education and public engagement to improve awareness and understanding. Communication Process for Industrial Heritage in Anshan City: Based on SMCR and McLuhan’s theories, the research identified various mediums like cultural activities, museums, and media as effective channels for conveying the value of industrial heritage. These platforms, along with interactive engagement such as workshops and guided tours, were found crucial in enabling the public to understand and experience the heritage firsthand. In conclusion, while there is recognition of industrial heritage in Anshan, there is a clear need for enhanced educational and publicity efforts to strengthen public awareness. The study’s findings offer important insights for the preservation and promotion of industrial heritage in Anshan city.